The relationship between psychological well-being and financial wellness - Nadilla, Faza Warda; Barida, Muya; Hasna, Hasna; Aziza, Nisrina Nurfi; Rahma, Hanif Fitria; Putri, Ega Seliyan; Aji, Archy Krisna (Universitas Islam Negeri Raden Intan Lampung, 2025)
Psychological well-being and financial wellness are two things that are interconnected in everyday life. Age and experience influence the relationship between psychological well-being and financial wellness. The aim of this research is to determine the relationship between psychological well-being and the financial wellness of facilitators climbing Mount Andong via Pendem. This research use a quantitative approach with a correlational research design. There were ten subjects in this study who were determined through convenience sampling. The data collection technique is non-test using a psychological well-being scale instrument consisting of 20 items and financial wellness scale instrument consisting 10 items. Data analysis technique use the product moment formula to test the relationship between psychological well-being and financial wellness. The results of the research can be concluded that there is a positive relationship resulting from the relationship between psychological well-being and financial well-being, which means that the higher the psychological well-being, the higher the financial wellness and conversely, the lower the psychological well-being, the lower the financial wellness. Therefore, counselors need to pay attention to the psychological well-being aspect and financial wellness through a series of guidance and counseling service activities as preventive and curative functions.